Effects of combined reading intervention on reading fluency and comprehension of three young adults with autism. - Laçin, Emre; Ceylan, Mustafa; Çetin, Erhan (International Journal of Developmental Disabilities, 2025)
This study evaluated the efficacy of a quadruple intervention package designed to enhance reading comprehension and accuracy in children diagnosed with Autism Spectrum Disorder (ASD). The intervention package comprised of four techniques, namely, repeated reading, word repetition, story map, and reader's theater. A single-subject research design with a multiple probe model and a between-participant probe phase was employed, and the participants of the study consisted of three male students diagnosed with ASD. The independent variables were the four aforementioned techniques, whereas the dependent variables were the participants' reading fluency and comprehension skills. The study consisted of baseline, implementation, full probe, generalization and follow-up sessions, and was conducted using the text 'Gamze and Her Friend' from the Informal Reading Inventory. The results indicated that the comprehensive intervention package improved the reading accuracy and comprehension of the three participants ASD, and this effect was sustained post-intervention.